Aspirin eugenol ester alleviates lipopolysaccharide-induced acute lung injury in rats while stabilizing serum metabolites levels - Tao, Qi; Zhang, Zhen-Dong; Qin, Zhe; Liu, Xi-Wang; Li, Shi-Hong; Bai, Li-Xia; Ge, Wen-Bo; Li, Jian-Yong; Yang, Ya-Jun (Frontiers in Immunology, 2022)
Aspirin eugenol ester (AEE) was a novel drug compound with aspirin and eugenol esterified. AEE had various pharmacological activities, such as anti-inflammatory, antipyretic, analgesic, anti-oxidative stress and so on. In this study, it was aimed to investigate the effect of AEE on the acute lung injury (ALI) induced by lipopolysaccharide (LPS) in rats. In vitro experiments evaluated the protective effect of AEE on the LPS-induced A549 cells. The tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-1β (IL-1β) were measured in the cell supernatant. The Wistar rats were randomly divided into five groups (n = 8): control group, model group (LPS group), LPS + AEE group (AEE, 54 mg∙kg−1), LPS + AEE group (AEE, 108 mg∙kg−1), LPS + AEE group (AEE, 216 mg∙kg−1). The lung wet-to-dry weight (W/D) ratio and immune organ index were calculated. WBCs were counted in bronchoalveolar lavage fluid (BALF) and total protein concentration was measured. Hematoxylin-Eosin (HE) staining of lung tissue was performed. Glutathione (GSH), glutathione peroxidase (GPx), catalase (CAT), antioxidant superoxide dismutase (SOD), total antioxidant capacity (T-AOC), lactate dehydrogenase (LDH), C-reactive protein (CRP), myeloperoxidase (MPO), malondialdehyde (MDA), macrophage mobility inhibitory factor (MIF), TNF-α, IL-6, and IL-1β activity were measured. The metabolomic analysis of rat serum was performed by UPLC-QTOF-MS/MS. From the results, compared with LPS group, AEE improved histopathological changes, reduced MDA, CRP, MPO, MDA, and MIF production, decreased WBC count and total protein content in BALF, pro-inflammatory cytokine levels, immune organ index and lung wet-dry weight (W/D), increased antioxidant enzyme activity, in a dose-dependent manner. The results of serum metabolomic analysis showed that the LPS-induced ALI caused metabolic disorders and oxidative stress in rats, while AEE could ameliorate it to some extent. Therefore, AEE could alleviate LPS-induced ALI in rats by regulating abnormal inflammatory responses, slowing down oxidative stress, and modulating energy metabolism.